1986
DOI: 10.1007/bf00711071
|View full text |Cite
|
Sign up to set email alerts
|

Down regulation of sodium channels in nerve terminals of spontaneously epileptic mice

Abstract: Tottering mice, in which a single gene lesion leads to prolonged hyperexcitability and spontaneous epilepsy, were studied to determine whether enhanced electrical activity leads to down regulation of sodium channels in central neurons. The number of sodium channels in synaptosomes, as assessed by saxitoxin binding, was decreased from 5.38 +/- 0.06 pmol/mg protein in coisogenic controls to 3.85 +/- 0.10 pmol/mg protein (P less than 0.001) in tottering mice without a change in the KD for saxitoxin. Neurotoxin-ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
48
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 17 publications
1
48
0
Order By: Relevance
“…Previous experiments have shown that local anesthetics and other sodium channel blocking drugs are indirect allosteric inhibitors of BTX binding and action (22)(23)(24)26), consistent with separate binding sites. Moreover, local anesthetics can block sodium channels activated by BTX without displacing the toxin, although higher concentrations are required than for unmodified sodium channels (27,28).…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…Previous experiments have shown that local anesthetics and other sodium channel blocking drugs are indirect allosteric inhibitors of BTX binding and action (22)(23)(24)26), consistent with separate binding sites. Moreover, local anesthetics can block sodium channels activated by BTX without displacing the toxin, although higher concentrations are required than for unmodified sodium channels (27,28).…”
Section: Resultsmentioning
confidence: 70%
“…Binding of toxins at neurotoxin receptor site 2 is enhanced allosterically by the binding of ␣-scorpion toxins to neurotoxin receptor site 3 (10), brevetoxins to neurotoxin receptor site 5 (11,14), and pyrethroid insecticides binding at an additional receptor site (13,14,21). Toxin binding at site 2 is inhibited allosterically by binding of tetrodotoxin at neurotoxin receptor site 1 (15) and by local anesthetics and related anticonvulsant and antiarrhythmic drugs (22)(23)(24)(25)(26). Local anesthetic block of BTX-modified sodium channels requires higher concentrations of drug than block of unmodified channels but does not displace BTX from its receptor (18,27,28).…”
mentioning
confidence: 99%
“…In addition to being intriguing candidate genes for neurological disorders based on their known function in neurotransmission, Na ? channel activity is known to be important in neurons in mouse models of spontaneous seizure disorders [34]. In 1998, a C121W substitution was reported [35] in a Na v 1 regulatory b1 subunit (SCN1B, chromosome 19q13) in a large GEFS ?…”
Section: Na V 1 and Gaba(a)rmentioning
confidence: 99%
“…13,14) Furthermore, compounds that bind to neurotoxin receptor site 2 are thought to block Na + channels in a use-dependent manner. [15][16][17] The concept of use dependency can be further explained by the modulated receptor hypothesis, 18) which proposes that drug binding is tighter to open or inactivated channels than to resting states. These observations suggest that site 2 Na + channel blockers may have a minimal effect on normal neuronal signaling but may act more effectively during ischemic conditions, where the membrane potential is persistently depolarized.…”
mentioning
confidence: 99%